ANALYSIS OF PROGNOSTIC FACTORS FOR FELINE MAMMARY TUMOURS (OVERVIEW INFORMATION) - D. Bilyi; A. Hierdieva; M. Herhaulov; V. Vakulyk (Наукові горизонти, 2020)
An analysis of the results of modern studies on the importance of clinical and pathomorphological factors as predictors of feline mammary tumours is presented. The urgency of the problem of predicting the development of cancer in this species is conditioned by the possibility of their use as biological models in human medicine, high level of incidence, significant share in the distribution of malignant types of tumours, and controversial issues of etiology and pathogenesis. Despite significant developments in the study of causal relationships with regard to mammary neoplasms, the use of different methodological approaches to assess the quantitative and qualitative characteristics of tumours, often in combination with insufficient sampling in groups does not allow to objectively assess the degree of malignancy and invasive potential both in a particular animal and in a group of patients, and therefore – to predict their behaviour. Generalization of available information on the peculiarities of the clinical course and pathomorphological changes in mammary tumours is necessary for further formation of a unified register of neoplasms in cats, which will be the basis for better understanding of the mechanisms of carcinogenesis, identification of promising biological targets, development and clinical implementation of pathogenetically based effective protocols for the treatment and prevention of cancer in cats. The lack of a unified approach to the verification of neoplasions makes it difficult, and in some cases impossible, to use cancer such predictors as histologic type, tumour size, clinical stage, angio- and lymphoinvasion, patient life expectancy and recurrence-free period as independent predictive factors. A large amount of clinical material has been accumulated, mainly presented in a descriptive form, without correlation with other causative factors. Along with the indicated predictors of carcinogenesis, in recent years, the role of cyclooxygenase-2 expression in the mechanisms of development and progression of feline mammary tumors has been actively studied, the influence on which allows obtaining a complex (multidirectional) therapeutic effect. Prospects for further research are the unification of clinical and pathomorphological diagnostic criteria and the establishment of a database of cats with cancer.